Is there a fragmentation in the oral and maxillofacial surgery research? A scientometric brief analysis of specialty's journals. - Javier Moraga (Universidad de Concepción., 2017)
Aim: To evaluate, using the Scopus database, the input and output citation pattern in the year 2015 for documents published in the five main oral and maxillofacial (OMS) journals. Methods: All document types published over the 2013-2015 period by the five main OMS journals: BJOMS, JOMS, IJOMS, JCMFS and JCFS were included. Citation and referencing data were extracted from the advanced search of Scopus. Results: A total of 2303 documents were published by the journals in 2015, and 3253 documents published in 2015 cited documents published by the journals in 2013 and 2014. Self-citation was 13.19% for the five journals as a whole, and 1024 (31.49%) documents cited journals from within the group. A total of 36,972 references were included in documents published in 2015 in the journals. Self-referencing was 6.56% for all journals as a group, and 7524 (20.35%) documents were from the group itself. From the top-20 referenced and citing journals, the presence of plastic and reconstructive surgery, and head and neck (otolaryngology) surgery journals is clear. This pattern was not the same across all the journals under study. Conclusion: There appears to be a "medical versus dental" fragmentation of research in the specialty, over a fragmentation by regions or countries.